SYSTEMS FOR MONITORING THE PRODUCTIVITY OF DAIRY FARM ANIMALS - Shopagulov, O.; Tretyakov, I.; Ismailova, A.; Gostin, A. (Academic Scientific Journal of Computer Science, 2021)
The relevance of this project lies in the fact that the use of modern digital, informational and intelligent technologies makes it possible to keep records of dairy productivity quickly and to respond to changes in the health of livestock in a timely manner. The result will increase the efficiency of resource potential use, as well as profitability and attractiveness of dairy cattle breeding for investors. The systems developed will also enable agricultural producers to make concrete decisions based on automated data analysis. The high quality of milk in the dairy farming industry, taking into account the feedback from the household to the consumer, ensures the competitiveness in the direction of the dairy industry. The article describes in detail a mathematical model for automating on-farm production control of dairy products, which will have an impact on the leveling of the commodity market. Also there are described the results of implementation of already developed software products for accounting of animal status on dairy farms of Northern Kazakhstan. As a result, some recommendations for the use of the developed software are given. In this way detailed results have been described for each farm, indicating the characteristics and status of the farms to date. The results obtained will be studied and considered by farmers at the local level to organise production processes. The implementation of this task will take place at the Seyfullin Kazakh Agrotechnical University. We have established a scientific group to develop and implement IT solutions for a large number of processes in agricultural production. This scientific programme is the first integrated solution aimed at introducing and adapting best practices in the application of digital technologies in dairy farming in Northern Kazakhstan.